2017
DOI: 10.1002/jobm.201600589
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of CRISPR‐Cas systems in Klebsiella genomes

Abstract: Prokaryotic CRISPR-Cas system provides adaptive immunity against invasive genetic elements. Bacteria of the genus Klebsiella are important nosocomial opportunistic pathogens. However, information of CRISPR-Cas system in Klebsiella remains largely unknown. Here, we analyzed the CRISPR-Cas systems of 68 complete genomes of Klebsiella representing four species. All the elements for CRISPR-Cas system (cas genes, repeats, leader sequences, and PAMs) were characterized. Besides the typical Type I-E and I-F CRISPR-Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
55
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 43 publications
12
55
1
3
Order By: Relevance
“…A total of 217 K. pneumoniae complete chromosomal sequences were extracted from GenBank (June 2019) and we identified that 81 of these (37%) carried CRISPR-Cas system on the chromosome. Of these 81, 45 were I-E and 36 were I-E * type ( Supplementary Table S3), consistent with previous reports (Ostria-Hernandez et al, 2015;Shen et al, 2017;Li et al, 2018). CP030878.1, CP020068.1, CP0016921.1, CP028929.1, CP024507.1, CP020854.1), ( * * CP018708.1, CP018702.1, CP018696.1, CP018720.1), ( * * * CP018687.1, CP018714.1, CP017986.1), (#CP022612.1, CP012754.1, CP006799.1), (##MG845201.1, MG845200.1) and (###CP030858.1, CP008933.1) and marked with asterisk or hashtag were the representative from each group showed in the figure.…”
Section: Analysis Of Crispr-cas System In K Pneumoniae Chromosomessupporting
confidence: 90%
See 2 more Smart Citations
“…A total of 217 K. pneumoniae complete chromosomal sequences were extracted from GenBank (June 2019) and we identified that 81 of these (37%) carried CRISPR-Cas system on the chromosome. Of these 81, 45 were I-E and 36 were I-E * type ( Supplementary Table S3), consistent with previous reports (Ostria-Hernandez et al, 2015;Shen et al, 2017;Li et al, 2018). CP030878.1, CP020068.1, CP0016921.1, CP028929.1, CP024507.1, CP020854.1), ( * * CP018708.1, CP018702.1, CP018696.1, CP018720.1), ( * * * CP018687.1, CP018714.1, CP017986.1), (#CP022612.1, CP012754.1, CP006799.1), (##MG845201.1, MG845200.1) and (###CP030858.1, CP008933.1) and marked with asterisk or hashtag were the representative from each group showed in the figure.…”
Section: Analysis Of Crispr-cas System In K Pneumoniae Chromosomessupporting
confidence: 90%
“…Several previous studies identified and analyzed chromosomal CRISPR-Cas systems in K. pneumoniae by analyzing 52 (Ostria-Hernandez et al, 2015), 68 (Shen et al, 2017) and 97 (Li et al, 2018) complete and draft genome sequences. Here, we analyzed 217 complete K. pneumoniae chromosomes available in GenBank for the distribution of CRISPR-Cas systems, their types, acquired spacers and relationship between presence and absence of CRISPR and plasmids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative set of putative novel cas genes was extracted from the genome of isolate INF256 (read accession: ERR1008719, genome assembly available in Figshare) and tBLASTx was used to detect the presence of NTUH--K2044--and INF256--like cas genes among all genomes (identity ≥85%, coverage ≥25%). Note that the INF256 cas genes were subsequently found to be highly similar to those of strain Kp52.145 reported during the course of this study 100 .…”
Section: Crispr/cas and Restriction--modification Systemssupporting
confidence: 76%
“…Spacer analysis was performed by BLAST and Geneious 18 . A phylogenetic UPGMA-based tree was constructed for CRISPR using MEGA7 19, 20 . Direct repeats and PAM conservation were assessed using WebLogo, RNA secondary structure was predicted using RNAfold 2123 .…”
Section: Methodsmentioning
confidence: 99%